Islamic Education with Ulul Albab Integration Paradigm: Pendidikan Islam Berparadigma Integrasi Ulul Albab - Sarkowi, Sarkowi (Universitas Muhammadiyah Sidoarjo, 2024)
This study wants to explain the importance of implementing the concept of Islamic education with the paradigm of ulul albab integration to produce human resources with ulul albab character. The choice of the ulul albab integration paradigm will provide certainty of the existence of Islamic education programs and practices to educate generations of Muslims, more specifically for example at the PTKI student level, as a generation that is prepared to be present and involved as prospective educators, mentors and leaders of the Ummah in the global era. . So, there needs to be real steps in improving the quality of students' human resources through strengthening and improving the quality of moderate education and learning that is integrated into the curriculum. The implemented curriculum needs to be supported by the existence of textbooks prepared using the ulul albab integration approach which supports the implementation of the RPS. In learning, it completely combines the cognitive, affective and motoric domains. These three domains must be stimulated in teaching and learning activities through various methods and integrated approaches by internalizing aspects of dzikir, fikir and amal sholeh. Keyword: Islamic Education, Integration Paradigm, Ulul albab